Kinetic Study of the Alkaline Hydrolysis of 1, n‐Bis(4‐cyanopyridinium)alkanes: Charge Density and New Conformational Effects on the Reactivity of 1, 3‐Bis(4‐cyanopyridinium)propane. Issue 8 (24th June 2013) - Fiori, Simone; de, Fernando Rodrigues; Tessaro, André Luiz; Meyer, Emerson; Caetano, Wilker; Politi, Mario José; Hioka, Noboru
ABSTRACT The alkaline hydrolysis reaction rates of 1, n‐bis(4‐cyanopyridinium)alkane derivatives Cnbis(CP)2+ with n = 3, 6, and 8 were studied and compared to the reaction rate of the N‐methyl‐4‐cyanopyridinium (MCP+). C6bis(CP)2+ and C8bis(CP)2+ obeyed the first‐order kinetic law. However for C3bis(CP)2+ data fitted to a consecutive two‐step model reaction, the observed rate constants (kobs) of C8bis(CP)2+ and C6bis(CP)2+ are approximately 50% and 100%, respectively, higher than those for MCP+, an effect mainly assigned to the higher charge density of these two derivatives. For C3bis(CP)2+, the kobs of the second (slow) step is almost twofold the value observed for C6bis(CP)2+, whereas the first (fast) step is approximately six times higher. As for MCP, the hydrolysis of Cnbis(CP)2+ generates pyridone (Po) and carbamidopyridinium (A+) units. For C3bis(CP)2+, however at pHs above 11.5, one additional product is formed. From the existence of the new product and the kinetic evidence, a "sandwiched‐type" complex with the OH− inserted between the rings is proposed. This structural effect in the C3bis(CP)2+ due to the conformational effect justifies the (i) two kinetic steps, (ii) high rate constants, (iii) high Po/A+ ratios, (iv) observed temperature and salt effects, and (v) the formation of the new product.